A Modified Technique For Expanded Polytetrafluoroethylene Shaping in Chin Augmentation. Issue 2 (March 2015) - Yang, Ping; Yang, Qingjian; Liu, Tianyi; Zeng, Jiping; Bi, Bo; Zhou, Yiqun; Guo, Yu; Chen, Liang
<x xml:space="preserve">Abstract</x> Objective In the current study, we restricted our focus on a modified approach to address the poor curved attachment of expanded polytetrafluoroethylenein chin augmentation. Method The implant is shaped generally in accordance with the chin, followed by 5-to-8 longitudinally parallel "V"-grooves carved in the median of posterior site where the implant directly attaches to the mandible. Thus, it enhances bend ductility of the prosthesis and renders better attachment from the curved surface of prosthesis to the mandibular embedded region. Results This procedure was performed in 15 patients. After follow-up for 2 to 6 months, there were no complications observed postoperatively including mobilization, dead space, subcutaneous dropsy, topical infection, or palpable edges in the subcutaneous area. Conclusions The introduction of longitudinally parallel V-groove technique provides an effective method for avoidance of increasing hardness, decreasing flexibility, and palpable edges after implantation.As a novel and effective technique, it is beneficial for better attachmentand satisfactory outcome without causing extra expenses.